INTERFERENSI LEKSIKAL BAHASA INGGRIS DALAM BAHASA INDONESIA PADA SURAT KABAR DI PEKANBARU - Raja Rachmawati (Madah: Jurnal Bahasa dan Sastra, 2012)
This article is aimed at describing English lexical interference int o bahasa Indonesia on newspapers that publish in Pekanbaru. some lexical interference aspects discussed in this paper such as based form of lexical element that consist of noun,verb, and adjective, derivative form of lexical element, and frase form of lexical element.This research used the descriptive method to get the accurate description about the interferences phenomenon of English into bahasa Indonesia on newspapers in Pekanbaru. The result shows that it occured in each column in the newspapers especially in News and Ec onomic Column that used as the data sources in this research, covering all word classes and word forms.Related to the matter above, it can be concluded that some factors influenced the interference such as: the habits of language user that always use the English term in their daily conversations.The other factor that caused interference was the need of synonym due to unavailable equivalent concepts in bahasa Indonesia.